Faecal haemoglobin concentration among subjects with negative FIT results is associated with the detection rate of neoplasia at subsequent rounds: a prospective study in the context of population based screening programmes in Italy. Issue 3 (27th August 2019) - Senore, Carlo; Zappa, Marco; Campari, Cinzia; Crotta, Sergio; Armaroli, Paola; Arrigoni, Arrigo; Cassoni, Paola; Colla, Rossana; Fracchia, Mario; Gili, Fabrizio; Grazzini, Grazia; Lolli, Roberto; et al.
Abstract : Objective: To estimate the predictive role of faecal haemoglobin (f-Hb) concentration among subjects with faecal immunochemical test (FIT) results below the positivity cut-off for the subsequent risk of advanced neoplasia (AN: colorectal cancer—CRC—or advanced adenoma). Design: Prospective cohort of subjects aged 50–69 years, undergoing their first FIT between 1 January 2004 and 31 December 2010 in four population-based programmes in Italy. Methods: All programmes adopted the same analytical procedure (OC Sensor, Eiken Japan), performed every 2 years, on a single sample, with the same positivity cut-off (20 µg Hb/g faeces). We assessed the AN risk at subsequent exams, the cumulative AN detection rate (DR) over the 4-year period following the second FIT and the interval CRC (IC) risk following two negative FITs by cumulative amount of f-Hb concentration over two consecutive negative FITs, using multivariable logistic regression models and the Kaplan-Meier method. Results: The cumulative probability of a positive FIT result over the subsequent two rounds ranged between 7.8% (95% CI 7.5 to 8.2) for subjects with undetectable f-Hb at the initial two tests (50% of the screenees) and 48.4% (95% CI 44.0 to 53.0) among those (0.7% of the screenees) with a cumulative f-Hb concentration ≥20 µg/g faeces. The corresponding figures for cumulative DR were: 1.4% (95% CI 1.3 to 1.6) and 25.5% (95% CI 21.4 to 30.2) for AN; 0.17% (95% CI 0.12 to 0.23) and 4.5% (95% CI 2.8 to 7.1) for CRC. IC risk was also associated with cumulative f-Hb levels. Conclusion: The association of cumulative f-Hb concentration with subsequent AN and IC risk may allow to design tailored strategies to optimise the utilisation of endoscopy resources: subjects with cumulative f-Hb concentration ≥20 µg/g faeces over two negative tests could be referred immediately for total colonoscopy (TC), while screening interval might be extended for those with undetectable f-Hb.